Pengaruh Kualitas Produk, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Sunscreen Azarine - Trimulyani, Sulistining; Cecelia, Ola Mariela (Yayasan Bina Internusa Mabarindo, 2024)
This research aims to identify, prove, and analyze the influence of product quality, price, and brand image on the purchasing decision of Azarine sunscreen. The research method applied is quantitative, using primary and secondary data sources. Teknik sampel yang digunakan adalah non-probability sampling dengan metode purposive sampling. Proses pengujian dalam penelitian ini mencakup pengujian validitas, pengujian reliabilitas, pengujian normalitas, pengujian multikolinearitas, pengujian heteroskedastisitas, analisis regresi linier berganda, uji-t, uji-F, dan uji koefisien determinasi (R²). The data used was obtained through a questionnaire, with 100 respondents who met the criteria as users or buyers of Azarine sunscreen. The testing was conducted using IBM SPSS version 27. The research shows that the variables of product quality and brand image have a positive and significant influence on purchasing decisions, while the price variable does not show a significant influence. Simultaneously, product quality, price, and brand image influence purchasing decisions. Overall, these three variables contribute 70.7% in predicting purchasing decisions, while the remaining 29.3% is influenced by other factors not analyzed in this study.